2013
DOI: 10.1017/s0021932013000503
|View full text |Cite
|
Sign up to set email alerts
|

Height as an Indicator of Economic Status in the Polish Territories Under Russian Rule at the Turn of the 19th to 20th Century

Abstract: Height is regarded as one of the indicators of environmental stress at population level, being an excellent barometer of standard of living. The aim of this study was to describe diversity in height among populations living in different regions of the Kingdom of Poland in terms of the economic factors in the second half of the 19th and early 20th century. This study examines the height of adult inhabitants from five guberniyas (provinces) of the Kingdom of Poland (Łomża, Warsaw, Radom, Kalisz and Płock) collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In the gentlefolk, the lower BMI in the 4th birth cohort could be due to an increasing trend in body height in this group. This phenomenon was also observed in the Prussian sector and the Kingdom of Poland at the same time (Kopczyński, 2007;Nowak, 2011;Czapla & Liczbińska, 2014). Individuals born in the last cohort were probably better nourished and taller than those born earlier, having as a result a smaller proportion of body weight to body height.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the gentlefolk, the lower BMI in the 4th birth cohort could be due to an increasing trend in body height in this group. This phenomenon was also observed in the Prussian sector and the Kingdom of Poland at the same time (Kopczyński, 2007;Nowak, 2011;Czapla & Liczbińska, 2014). Individuals born in the last cohort were probably better nourished and taller than those born earlier, having as a result a smaller proportion of body weight to body height.…”
Section: Discussionmentioning
confidence: 72%
“…There is still little information about the relationship between the well-being, nutritional habits and BMIs of the 19th century population of the Polish lands. Research on historical Polish populations from the late 19th and early 20th centuries has been limited to analyses of determinants of body height as indicators of the prevailing socioeconomic conditions (Czekanowski, 1930;Kopczyński, 2005Kopczyński, , 2006Kopczyński, , 2007Kopczyński, , 2011Czapla & Liczbińska, 2014), or to secular trends in body height (Nowak, 2011;Czapla & Liczbińska, 2014). There have been no studies on a possible link between socioeconomic status and BMI by social group among the adult Polish population.…”
Section: Introductionmentioning
confidence: 99%
“…Secular trends in the heights of the Polish population from the 19 th century to modern times have been widely discussed (Bielicki and Szklarska 1999;Czapla and Liczbińska 2014;Czapla et al 2019;Kołodziej et al 2015;Łopuszańska-Dawid et al 2019). The positive secular trend in height was interrupted during conditions associated with WWI and WWII, but was re-established after WWII: 195519671975=160.39 cm (Górny and Dobrzańska 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Their analysis of the historic data revealed a significant association between final body height and socioeconomic status among the different provinces. The authors concluded that the socioeconomic conditions in a certain region exert significant effects on the quality of life, which is reflected in biological variables such as height (Czapla & Liczbińska 2014).…”
Section: The Systematic Analysis: Psychosocial Factors and Physical Gmentioning
confidence: 99%
“…Taking the findings of the previously reviewed studies together, it should be noted that a general association between socioeconomic status and growth outcomes could be observed. Even across various temporal and cultural contexts, taller mean stature and lower frequencies of stunting were associated with higher socioeconomic status (Chistiansen 1975;Bielicki et al 1981;Bogin et al 2002;Wamani et al 2007;El Taguri et al 2009;Mushtaq et al 2011;Nguyen et al 2013;Czapla & Liczbińska 2014;Keino et al 2014;Vercelotti et al 2014;Krishna et al 2015;Schwekendiek 2017;Green et al 2018;Scheffler et al 2020). Despite their agreement on a general association between socioeconomic status and growth, the authors discussed different possible explanations for this trend.…”
Section: The Systematic Analysis: Psychosocial Factors and Physical Gmentioning
confidence: 99%